2019
DOI: 10.1007/s00134-019-05772-1
|View full text |Cite
|
Sign up to set email alerts
|

154 compared to 54 mmol per liter of sodium in intravenous maintenance fluid therapy for adult patients undergoing major thoracic surgery (TOPMAST): a single-center randomized controlled double-blind trial

Abstract: Purpose: To determine the effects of the sodium content of maintenance fluid therapy on cumulative fluid balance and electrolyte disorders. Methods: We performed a randomized controlled trial of adults undergoing major thoracic surgery, randomly assigned (1:1) to receive maintenance fluids containing 154 mmol/L (Na154) or 54 mmol/L (Na54) of sodium from the start of surgery until their discharge from the ICU, the occurrence of a serious adverse event or the third postoperative day at the latest. Investigators,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 42 publications
(27 citation statements)
references
References 41 publications
0
27
0
Order By: Relevance
“…Acute, hospital acquired hyponatremia has been associated with the administration of hypotonic, maintenance type fluids in human patients (39,42,43). Randomized controlled trials comparing isotonic crystalloids with hypotonic crystalloids as ongoing maintenance fluid therapy in adult humans and pediatric patients have shown isotonic crystalloids to be safe and is associated with a lower incidence of hyponatremia (44)(45)(46)(47).…”
Section: Replacement Vs Maintenance Fluidsmentioning
confidence: 99%
“…Acute, hospital acquired hyponatremia has been associated with the administration of hypotonic, maintenance type fluids in human patients (39,42,43). Randomized controlled trials comparing isotonic crystalloids with hypotonic crystalloids as ongoing maintenance fluid therapy in adult humans and pediatric patients have shown isotonic crystalloids to be safe and is associated with a lower incidence of hyponatremia (44)(45)(46)(47).…”
Section: Replacement Vs Maintenance Fluidsmentioning
confidence: 99%
“…Many clinicians suggest to use isotonic maintenance fluids in order to avoid the risk of hyponatremia and cerebral edema [40]. On the contrary, other authors promote the use of hypotonic fluids in order to avoid "water and salt intoxication" [41,42].…”
Section: Discussionmentioning
confidence: 99%
“…In a study with 15,802 intensive care patients, Self et al found lower rates of renal failure, use of dialysis, and lower total mortality in those receiving fluid therapy with balanced crystalloid solutions (Self et al 2018 ). Regarding the development of hyperchloremia, solutions associated with a certain risk are not only those used for volume replacement as part of initial circulatory resuscitation (Bandak and Kashani 2017 ; Sen et al 2017 ) but, also, solutions employed for the dilution and reconstitution of the drugs administered (e.g., antibiotics), vitamin therapy, flushing catheters and sets, and so on (Van Regenmortel et al 2019 ; Van Regenmortel et al 2018 ). The effect of the implementation of new strategies reducing the rates of administering high-chloride solutions was well documented in the study of Yuons et al, where the implementation of control measures in fluid therapy (administration of Hartman’s solution, Plasmalyte, and 20% albumin with low Cl − content instead of the uncontrolled administration of various types of solutions) was followed by a statistically significant decrease in the rates of acute renal failure and the use of dialysis (Yunos et al 2012 ).…”
Section: Discussionmentioning
confidence: 99%